2020
DOI: 10.1007/s00167-020-06274-0
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the changing patterns in clinical and academic activities of the orthopedic residents during COVID-19 pandemic: a cross-sectional survey

Abstract: Purpose The COVID-19 pandemic has presented an unprecedented challenge to the orthopedic residency training programs to adapt to a form of a web-based learning process and simulation-based training. This study focusses on the viewpoint of the orthopedic residents to the paradigm shift in clinical care as well as the academic activities. Methods An anonymous questionnaire was created in an online survey generator and was sent through e-mail to 227 orthopedic residents of seven tertiary care centres in North Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 15 publications
(19 reference statements)
0
53
2
3
Order By: Relevance
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety (n = 103), depression (n = 73), stress (n = 68), fear (n = 61), burnout (n = 25), mental distress/health (n = 21), and post-traumatic stress disorder (PTSD) (n = 14) (Additional File 3). Most COVID-19 studies reported on physicians from USA (n = 23) [41,52,66,70,77,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107], China (n = 22) [15, 49, 54-56, 65, 68, 73, 86, 89, 102, 108-118] followed by India (n = 21) [40,50,58,63,67,71,102,[119][120][121][122][123][124][125][126][127][128][129][130][131][132] [41,52,…”
Section: Experiences With Physician Psychological Symptoms During Infectious Disease Outbreaksmentioning
confidence: 99%
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety (n = 103), depression (n = 73), stress (n = 68), fear (n = 61), burnout (n = 25), mental distress/health (n = 21), and post-traumatic stress disorder (PTSD) (n = 14) (Additional File 3). Most COVID-19 studies reported on physicians from USA (n = 23) [41,52,66,70,77,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107], China (n = 22) [15, 49, 54-56, 65, 68, 73, 86, 89, 102, 108-118] followed by India (n = 21) [40,50,58,63,67,71,102,[119][120][121][122][123][124][125][126][127][128][129][130][131][132] [41,52,…”
Section: Experiences With Physician Psychological Symptoms During Infectious Disease Outbreaksmentioning
confidence: 99%
“…We deemed 18 articles to be relevant. The articles included are those of van der Keylen et al [ 10 ], Soy-Muner [ 11 ], Daniel [ 12 ], Moszkowicz et al [ 13 ], Yılmaz et al [ 14 ], Al-Balas et al [ 15 ], Sharma [ 16 ], George [ 17 ], Kim et al [ 18 ], Sabharwal et al [ 19 ], Sutiah et al [ 20 ], Scull et al [ 21 ], Barik et al [ 22 ], Khalaf [ 23 ], Mansoor [ 24 ], Ibrahim et al [ 25 ], Lowenthal et al [ 26 ], and Chick et al [ 27 ]. Of these 18 articles, 8 are from Asia, 4 from America, 4 from Europe, 1 from Africa, and 1 from Oceania.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond lessons, ICTs have been used to conduct examinations or train students by remote evaluations [ 16 , 22 , 24 ]. An app is used in combination with a browser for written examinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the current scenario of the COVID-19 pandemic, there has been a shift in the paradigm especially in the teaching of the residents [ 10 , 11 ]. Earlier, face-to-face interaction was considered the gold standard for medical education, and the need for maintaining up-to-date knowledge in the field was made possible by subscription to various online specialty-specific journals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%